2009
DOI: 10.1093/mollus/eyp028
|View full text |Cite
|
Sign up to set email alerts
|

Egg retention and ovoviviparity in clausiliids of the genus Vestia P. Hesse (Gastropoda: Clausiliidae)

Abstract: The reproductive biology of three Carpathian clausiliids of the genus Vestia [V. gulo (E.A. Bielz, 1859), V. elata (Rossma¨ssler, 1836) and V. turgida (Rossma¨ssler, 1836)] was studied using two methods: (1) the presence of eggs was examined in uteri of snails collected in the wild; and (2) the reproduction of snails was observed for 2-4 years under laboratory conditions. All three species retained eggs (ovoviviparity sensu lato), but there was a variation in the stage of the development of embryos among the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…14 days). The eggs of other Vestia species kept at the same laboratory hatched after shorter time of external development (V. gulo: 7-10 days; V. elata: 2-4 days; V. turgida: 0-2 days), and immediately after egg deposition big, shelled embryos were visible through the egg envelopes (Sulikowska-Drozd 2008, 2009). In the Carpathian Vestia species anatomical examination of adults revealed the presence of developing embryos in reproductive tract, thus confirming their egg retaining reproductive mode.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…14 days). The eggs of other Vestia species kept at the same laboratory hatched after shorter time of external development (V. gulo: 7-10 days; V. elata: 2-4 days; V. turgida: 0-2 days), and immediately after egg deposition big, shelled embryos were visible through the egg envelopes (Sulikowska-Drozd 2008, 2009). In the Carpathian Vestia species anatomical examination of adults revealed the presence of developing embryos in reproductive tract, thus confirming their egg retaining reproductive mode.…”
Section: Discussionmentioning
confidence: 99%
“…Larger egg batches were recorded in V. gulo and B. fallax indicating a correlation with adult size which is larger in these species (Table 3). Among medium sized clausiliids (V. r. moravica, V. turgida, V. elata and B. stabilis) the size of egg batch/litter varied slightly: oviparous P. stabilis and V. r. moravica laid usually 5-8 and 4-6 eggs, respectively; egg-retaining V. elata produced 2-7 eggs at a time, while V. turgida delivered 2-5 neonates (Sulikowska-Drozd 2009;Sulikowska-Drozd & Maltz 2012b). Mean values of batch/litter size indicated that brooding species produced usually fewer offspring per reproductive event than oviparous clausiliids (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations